New Measurement of the anomalous magnetic moment of the positive muon - Carey, Robert M.; Grossmann, Alex; Gerhäuser, Jürgen; Jungmann, Klaus; Walter, P. von; Putlitz, Gisbert zu (Physical review letters, 1999)
The muon anomalous magnetic moment has been measured in a new experiment at Brookhaven. Polarized muons were stored in a superferric ring, and the angular frequency difference, ωa, between the spin precession and orbital frequencies was determined by measuring the time distribution of high-energy decay positrons. The ratio R of ωa to the Larmor precession frequency of free protons, ωp, in the storage-ring magnetic field was measured. We find R=3.707220(48)×10−3. With μμ/μp=3.18334547(47) this gives aμ+=1165925(15)×10−9 ( ±13ppm), in good agreement with the previous CERN measurements for μ+ and μ− and of approximately the same precision.